The productivity effect of secondary schooling a bit of evidence - Alicias, Eduardo R.
This paper seeks to adduce a bit of evidence on the productivity effect of specific level of schooling, the completion of secondary level. This paper is based on data gathered in connection with a larger study. The findings in this study imply a greater role of the schooling process on productivity improvements. Economic growth enhanced by making the schooling process more efficient and effective.
Keywords: Labor productivity -- Philippines; Human capital -- Philippines